PENEGAKAN HUKUM PADA TINGKAT PENYIDIKAN TERHADAP PELAKU TINDAK PIDANA PENGEDARAN SEDIAAN FARMASI TANPA IZIN DI KOTA SOLOK - Defrianto, Defrianto; Rosmely, Wirna (UNES Journal of Swara Justisia, 2019)
Article 197 Law number 36 of 2009 concerning Health stipulates that "everyperson who intentionally produces or distributes pharmaceutical preparations and / ormedical devices that do not have a distribution permit is given criminal sanctions andfines". For this matter, it is necessary to grant permits in the distribution ofpharmaceutical preparations, to protect the public from pharmaceutical preparations thatdo not meet the requirements, protect the public from misuse and misuse of pharmaceuticalpreparations and medical devices. This needs supervision from the Police in supervisingpharmaceutical preparations, this is done by Satreskrim Solok City Police, who havereceived a Police Report from the community on December 13, 2016. This research is adescriptive analytical study. Adapaun the results of research on law enforcement at thelevel of investigation of perpetrators of criminal acts of distribution of pharmaceuticalpreparations without permission in the city of Solok occurred in the report on December13, 2016, after the report was received, Satok District Police issued LP / 89 / A / XII /2016-SEKTA, then Investigation, Investigation, Examination of witnesses, Information ofExperts, Suspects and determining the elements of the Criminal Act which are suspected ofbeing violated by the suspect. Secondly, the obstacle encountered by Solres Kota police inlaw enforcement against criminal acts circulating pharmaceutical preparations withoutpermission in Solok City: a) Limited budget funds; b) Number of Investigators who are notbalanced with the breadth of work area; c) Modus Operandi carried out by the perpetratoris always changing; d) Other agencies that are less cooperative; e) expert witnesses aredifficult to bring; and f) Difficulties in bringing and presenting witnesses concerned withcases of pharmaceutical preparations without permission to eat the old procedure, becausethere are several witnesses who do not want to come or even not be asked to be questionedby members of the auxiliary investigators who examine. Third, efforts to overcome theobstacles in law enforcement against criminal acts circulating pharmaceuticalpreparations without permission in the city of Solok, by making repressive efforts andPreventive efforts.